The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1037/xlm0000054
|View full text |Cite
|
Sign up to set email alerts
|

No solid empirical evidence for the solid (serial order learning impairment) hypothesis of dyslexia.

Abstract: This article reports on 2 studies that attempted to replicate the findings of a study by Szmalec, Loncke, Page, and Duyck (2011) on Hebb repetition learning in dyslexic individuals, from which these authors concluded that dyslexics suffer from a deficit in long-term learning of serial order information. In 2 experiments, 1 on adolescents (N = 59) and 1 on children (N = 57), no empirical evidence was obtained for impaired Hebb learning in dyslexics, whether the same data-analytical procedure as Szmalec et al. w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 83 publications
3
40
1
Order By: Relevance
“…Of the few relevant studies in children, the findings support the conclusion that there is a serial order memory deficit (Martinez Perez, Majerus, Mahot, & Poncelet, 2012) and refute the suggestion that there is not (Staels & van den Broeck, 2014, 2015). At the same time, given that the magnitude of the serial order memory deficit was dependent on a number of test factors in our study (especially the modality and the predictability of the list length), it is not terribly surprising that, under some circumstances, the deficit has not been observed.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Of the few relevant studies in children, the findings support the conclusion that there is a serial order memory deficit (Martinez Perez, Majerus, Mahot, & Poncelet, 2012) and refute the suggestion that there is not (Staels & van den Broeck, 2014, 2015). At the same time, given that the magnitude of the serial order memory deficit was dependent on a number of test factors in our study (especially the modality and the predictability of the list length), it is not terribly surprising that, under some circumstances, the deficit has not been observed.…”
Section: Discussionmentioning
confidence: 52%
“…Several previous studies have examined nonverbal, as well as verbal, serial order short-term memory mechanisms in adults who had developmental dyslexia using a variety of methods, and have found some deficits in serial order memory (in Dutch, Hachmann et al, 2014; in Finnish, Laasonen et al, 2012; in French, Martinez Perez et al, 2013, 2015; in English, Romani, Tsouknida, & Olson, 2015; Wang, Xuan, & Jarrold, 2016). There are very few relevant studies with children, and they have differed in suggesting that there is a serial order memory deficit (in French: Martinez Perez, Majerus, Mahot, & Poncelet, 2012) or that there is not (with a similar population: Staels & van den Broeck, 2014, 2015). …”
Section: Recent Literature On Serial Order Memory Deficits In Dyslexiamentioning
confidence: 99%
“…As documented in the introduction, many studies have reported deficits on a range of implicit learning measures in children with language impairment (Hedenius, ; Hsu & Bishop, ; Lum et al., ) or dyslexia (Howard et al., ; Vicari et al., ). However, the findings from previous studies are distinctly mixed, with many null results (Gabriel et al., ; Lum & Bleses, ; Majerus, ; Staels & Van den Broeck, ). Methodologically, most studies in this area share a number of undesirable characteristics: (1) the studies use extreme group designs; (2) sample sizes are small, giving low statistical power; (3) only a single measure, or a limited range of measures of learning and memory are used in any one study; (4) the studies do not report reliability estimates for the measures of learning.…”
Section: Discussionmentioning
confidence: 93%
“…() also found dyslexic adults to be impaired on a non‐verbal visuo‐spatial Hebb task using sequences of dot locations, suggestive of a domain‐general impairment. However, once again findings are mixed and Staels and Van den Broeck () found no evidence of impaired learning on a verbal Hebb task in adolescents or children with dyslexia and nor did Majerus et al. () in a study of children with SLI.…”
Section: Introductionmentioning
confidence: 97%
“…More recently, some researchers have highlighted the contribution to decoding skills of either serial order memory capacity (e.g., Majerus, Poncelet, Greffe, & Van der Linden, 2006;Martinez Perez, Majerus, & Poncelet, 2012a) or the consolidation (or transfer) of serial-order information into a stable LTM trace (Szmalec, Loncke, Page, & Duyck, 2011; but see Staels & Van den Broeck, 2014a). For instance, in a 1-year longitudinal study starting in kindergarten, phonemic awareness (assessed by a phoneme identification task) and serial order STM (measured by a serial order reconstruction task 8 ), but not item STM (measured by monosyllabic nonword repetition under articulatory suppression), predicted independent variance in decoding abilities in first grade, even after controlling for nonverbal reasoning, vocabulary, and initial letter knowledge (Martinez Perez, Majerus, Mahot, & Poncelet, 2012b; see also Nithart et al, 2011).…”
Section: Learning To Read: a Task Engaging Working Memorymentioning
confidence: 99%